Advancing remote sensing and machine learning‐driven frameworks for groundwater withdrawal estimation in Arizona: Linking land subsidence to groundwater withdrawals. Issue 11 (14th November 2022) - Majumdar, Sayantan; Smith, Ryan; Conway, Brian D.; Lakshmi, Venkataraman
Abstract: Groundwater plays a crucial role in sustaining global food security but is being over‐exploited in many basins of the world. Despite its importance and finite availability, local‐scale monitoring of groundwater withdrawals required for sustainable water management practices is not carried out in most countries, including the United States. In this study, we combine publicly available datasets into a machine learning framework for estimating groundwater withdrawals over the state of Arizona. Here we include evapotranspiration, precipitation, crop coefficients, land use, annual discharge, well density, and watershed stress metrics for our predictions. We employ random forests to predict groundwater withdrawals from 2002 to 2020 at a 2 km spatial resolution using in situ groundwater withdrawal data available for Arizona Active Management Areas (AMA) and Irrigation Non‐Expansion Areas (INA) from 2002 to 2009 for training and 2010–2020 for validating the model respectively. The results show high training ( R 2 ≈ 0.9 R^2≈ 0.9 ) and good testing ( R 2 ≈ 0.7 R^2≈ 0.7 ) scores with normalized mean absolute error (NMAE) ≈ 0.62 and normalized root mean square error (NRMSE) ≈ 2.34 for the AMA/INA region. Using this method, we spatially extrapolate the existing groundwater withdrawal estimates to the entire state and observe the co‐occurrence of both groundwater withdrawals and land subsidence in South‐Central and Southern Arizona. Our model predicts groundwater withdrawals in regions where production wells are present on agricultural lands and subsidence is observed from Interferometric Synthetic Aperture Radar (InSAR), but withdrawals are not monitored. By performing a comparative analysis over these regions using the predicted groundwater withdrawals and InSAR‐based land subsidence estimates, we observe a varying degree of subsidence for similar volumes of withdrawals in different basins. The performance of our model on validation datasets and its favourable comparison with independent water use proxies such as InSAR demonstrate the effectiveness and extensibility of our combined remote sensing and machine learning‐based approach. Abstract : Groundwater plays a crucial role in sustaining global food security but is being over‐exploited in many basins of the world and the extent of water use is unknown in most regions. In this work, we successfully demonstrated a method to estimate groundwater use by integrating satellite datasets with machine learning. This work could aid water managers in putting sustainability efforts into practice.